The Influence of Work Motivation and Work Environment on Turnover Intention with Job Satisfaction as A Mediator Among Cleaning Service Employees at PT. Bringin Karya Sejahtera in Bali - I Ketut Mudhiarta; Ida Ayu Putu Widani Sugianingrat; Cokorda Gede Bayu Putra (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
The purpose of this research is to examine the relationship and influence between work motivation and work environment on turnover intention, with job satisfaction as a moderating variable. The subjects of this study are Cleaning Service workers at PT Bringin Karya Sejahtera, Denpasar branch. The total number of respondents is 68 individuals. The analysis techniques used are descriptive analysis and SEM-PLS analysis using Smart-PLS 4.0. The results of this study indicate that work motivation has a negative and significant effect on turnover intention, suggesting that the higher the work motivation of employees, the lower their desire to leave their jobs. The work environment does not have a significant effect on turnover intention, indicating that the work environment does not significantly influence employees' intention to quit their jobs. Work motivation has a positive and significant effect on job satisfaction, meaning that the higher the work motivation of employees, the greater their job satisfaction. The work environment also has a positive and significant effect on job satisfaction, indicating that a more comfortable work environment leads to higher employee satisfaction. Job satisfaction has a negative and significant effect on turnover intention, suggesting that the higher the level of job satisfaction among employees, the lower their desire to leave their jobs. Work motivation and the work environment have an indirect influence on turnover intention with job satisfaction as a mediating variable, indicating that low work motivation and a poor work environment indirectly increase employees' desire to quit.